(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
The orthopteran insect group is poorly explored, and there is no confirmed record of any species under the Schizodactylidae family in Bangladesh. Here, we provided the first confirmed record of Schizodactylus monstrous under the family Schizodactylidae. A single individual of a species belonging to the family, a nymph of Schizodactylus monstrous, was sighted from a protected area of the country. J. Bangladesh Acad. Sci. 48(2); 161-163: December 2024